2011
DOI: 10.1002/jsfa.4445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lard on the formation of volatiles from the Maillard reaction of cysteine with xylose

Abstract: The addition of lipid was inhibitory to the formation of most sulfur-containing compounds in the Maillard reaction. Furthermore, Maillard reaction products influenced the formation of products from lipid oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 39 publications
2
35
1
Order By: Relevance
“…However, for the compounds form Maillard reaction, it seemed that only two compounds (2‐acetyfuran and 2‐methyl thiophene) covaried with above three MFS samples. These results are in agreement with the findings of Xu et al , who showed that oxidized lard had more important influence on the compounds formed from the cysteine–xylose reaction to a much greater extent than the addition of fresh lard. The results are also in accordance with the research of Mottram , who confirmed that lipid performed a quenching effect on the quantities of heterocyclic compounds formed from the Maillard reaction.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, for the compounds form Maillard reaction, it seemed that only two compounds (2‐acetyfuran and 2‐methyl thiophene) covaried with above three MFS samples. These results are in agreement with the findings of Xu et al , who showed that oxidized lard had more important influence on the compounds formed from the cysteine–xylose reaction to a much greater extent than the addition of fresh lard. The results are also in accordance with the research of Mottram , who confirmed that lipid performed a quenching effect on the quantities of heterocyclic compounds formed from the Maillard reaction.…”
Section: Resultssupporting
confidence: 93%
“…These results were consistent with the results of Whitfield , who indicated that the presence of lipid may decrease the amount of certain sulfur‐containing compounds. Xu et al drew the same conclusion. He added non‐oxidized and oxidized lard into cysteine and xylose model systems, and found that 19 of the Maillard reaction‐derived compounds were formed at lower levels compared with the addition of non‐oxidized lard.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The model reaction mixture of cysteine and ribose alone had a strong smell of sulphur; however, when either a phospholipid or a triglyceride was included, an evident meaty aroma was perceived . Up until now, there have been lots of reports on the effect of a lipid on volatile compounds generated in the reaction model containing cysteine and reducing sugars. The general result is that inclusion of lipids in the reaction system of cysteine and reducing sugars tends to reduce the level of sulphur and heterocyclic compounds derived solely from the Maillard reaction, while the Maillard reactions of cysteine and reducing sugars would reduce the level of aliphatic carbonyl compounds derived from lipid oxidation and degradation e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It explains a large part of the sensory properties, aroma, and taste of cooked products . The typical aroma of cooked products is derived from an extremely complex mixture of volatile compounds, which are mainly derived in two ways . One is by adding flavoring material to the meat flavor after the thermal reaction, and the other is reducing the sugar involved in the Maillard reaction …”
Section: Introductionmentioning
confidence: 99%